Dampak Keberadaan Agrowisata California Terhadap Kondisi Sosial Ekonomi Masyarakat Desa Cialam Jaya - Lestari, Febi Silvia; Yunus, Lukman; Slamet, Agustono (PT. Pubsains Nur Cendekia, 2023)
The development of tourism activities in Cialam Jaya Village is considered to have a lot impacts on the social and economic conditions around the tourist area, especially the residents of Cialam Jaya Village. The purpose of this study was to examine the social impact of the residents of Cialam Jaya Village with the existence of California Cialam Agrotourism and to examine the economic impact of the residents of Cialam Jaya Village with the existence of California Agrotourism. The population in this study was the people of Cialam Jaya Village and the sample in this study was 22 people selected using purposive sampling technique. Data analysis uses descriptive method with a qualitative approach. The results of this research show that the existence of California Agrotourism has an impact on the social conditions of the community including mutual cooperation activities, harmony and interaction with tourists, and does not have an impact on the socio-economic conditions of the community.